Secretory structures and cytochemical investigation of the leaf of Phlomis fruticosa, a seasonally dimorphic subshrub. Secreting activity of the leaf-originating calluses - Nikolakaki, A.; Christodoulakis, N.S. (Flora: Morphology, Distribution, Functional Ecology of Plants, 2007)
Various species of the genus Phlomis have been reported to produce metabolites demonstrating significant pharmacological efficiency. In mature summer leaves of Phlomis fruticosa several secretory cells and structures were detected. A spectrum of compounds was localized histochemically within them. Calluses produced from leaf-cell cultures were histochemically investigated as well. Callus cells, although of low-differentiation, are synthetically active and produce various compounds. Many of them could be of pharmaceutical interest. © 2007 Elsevier GmbH. All rights reserved.
Keywords: essential oil; Essential oils; Histochemistry; leaf; Phlomis; Phlomis fruticosa; secondary metabolite; Secondary metabolites; secretion; Secretory structures; shrub; Tissue culture